2009
DOI: 10.3922/j.psns.2009.2.015
|View full text |Cite
|
Sign up to set email alerts
|

Strain and sex differences in fear conditioning: 22 kHz ultrasonic vocalizations and freezing in rats.

Abstract: Strain and sex differences in fear conditioning were investigated in two commonly used laboratory rats: Sprague Dawleys and Long-Evans. Twenty-two kHz ultrasonic vocalization (USV) distress calls and freezing behavior were used to measure fear responses to contextual and auditory conditioned stimuli (CSs), which were previously paired with a footshock unconditioned stimulus (US). Both strain and sex had significant effects on USVs and freezing during training and subsequent context and tone tests. Overall, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
3
29
1
Order By: Relevance
“…In fact, vocalizations at this point were so low that the lack of significance between the two groups could be explained by a floor effect. Meanwhile, freezing remained high in both conditions, evidencing that freezing and vocalizations are differently responsive to environmental factors as previously reported (Jelen et al, 2003 ; Graham et al, 2009 ). The fact that STN lesions induce dissociation between the two behavioral responses further supports the view that they may reflect separable aspects of aversive processes.…”
Section: Discussionsupporting
confidence: 84%
“…In fact, vocalizations at this point were so low that the lack of significance between the two groups could be explained by a floor effect. Meanwhile, freezing remained high in both conditions, evidencing that freezing and vocalizations are differently responsive to environmental factors as previously reported (Jelen et al, 2003 ; Graham et al, 2009 ). The fact that STN lesions induce dissociation between the two behavioral responses further supports the view that they may reflect separable aspects of aversive processes.…”
Section: Discussionsupporting
confidence: 84%
“…Several aspects, however, argue against such a conclusion: For one, the positive relationships between pup USV and adult anxiety were observed in selectively‐bred lines of rats, but were either not found in “normal” stocks (WU, Wöhr & Schwarting, ) or were even negatively related to adult anxiety there (Schwarting & Pawlak, ). Second, it was found that adult SD rats emitted more 22‐kHz calls and froze more in a fear‐conditioning paradigm than LE rats (Graham et al, ) or that SD rats showed more 22‐kHz calls and immobility in a social intruder paradigm than WU rats (Walker et al, ). We also found more 22‐kHz USV in a fear‐conditioning paradigm in SD than WU rats (Schwarting, ), and Turner and Burns () considered adult LE rats to be more anxious than SD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it was found that adult SD rats emitted more 22-kHz calls and froze more in a fear-conditioning paradigm than LE rats (Graham et al, 2009) or that SD rats showed more 22-kHz calls and immobility in a social intruder paradigm than WU rats (Walker et al, 2009).…”
Section: Functional Aspects Of Ultrasonic Vocalizations In Pupsmentioning
confidence: 99%
See 1 more Smart Citation
“…While female sex remains a risk factor, the sexual dimorphism present in the acquisition (Inslicht et al, 2013), presentation (Olff et al, 2007;Hourani et al, 2015), and treatment efficacy (Blain et al, 2010) of PTSD suggests that there are underlying biological differences based on sex that need to be investigated separately in both sexes (Cahill, 2003a(Cahill, ,b, 2006Pineles et al, 2017). Similarly to humans, rodent models of PTSD-associated behaviors show sex differences in response to trauma (Faraday, 2002;Adamec et al, 2006;Graham et al, 2009;Cohen and Yehuda, 2011;Toth et al, 2016;Pineles et al, 2017;Deslauriers et al, 2019). The RISP model was developed in male rats and we hypothesize that female rats will require different behavioral parameters for classification and PTSD-phenotyping.…”
Section: Developing a Female Animal Model To Study Susceptibility Facmentioning
confidence: 99%